Can Spectrophotometry Be Used to Quantify Zingiberene Sesquiterpenoids in Tomato Leaflet Extracts? - Mohammad Dawood (MDPI AG, 2021)
The presence of 7-epi zingiberene in wild tomatoes has been associated with arthropod resistance. Consequently, tomato breeders are attempting to introgress 7-epi zingiberene from wild to cultivated tomato requiring quantification of zingiberene. 7-Epi zingiberene likely absorbs UV light due to its conjugated double bonds and others have claimed that measurement of absorbance at 270 nm of tomato leaflet washes can be used to quantify zingiberene. However, this claim has never been critically evaluated. We initially evaluated this claim in an interspecific hybrid tomato generation that was segregating widely for zingiberene. Results indicated that the method does not obey the Beer–Lambert law. Consequently, we examined in detail aspects of the UV-absorbance of isolated zingiberenoids and leaflet washes obtained from parents and interspecific generations that were segregating for 7-epi zingiberene. Results indicated that isolated zingiberenoids, as well as leaflet washes containing zingiberenoids, have broad absorbance spectra with a λmax of 264 nm. For isolated zingiberenoids, the relationship between abundance and absorbance at 264 nm did obey the Beer–Lambert law. Average absorbance spectra for leaflet washes from interspecific generation plants showed subtle λmax shifts. Furthermore, the relationship between absorbance at 264 nm and zingiberenoid content of these generations did not obey the Beer–Lambert law. The use of multiple wavelengths for estimation of zingiberenoids in these breeding generations was explored and the inclusion of additional absorbances at one or two wavelengths always improved estimates. However, identified wavelength(s) differed among generations. Taken together, the results indicate that measurement of absorbance of tomato leaflet washes at a single wavelength is not a reliable quantitative estimate of zingiberenoids in leaflet washes. Estimates can be improved by utilizing absorbance at multiple wavelengths, but the particular wavelengths will vary among generations. Lastly, measurement of absorbance may be useful for identifying those relatively rare individuals in a generation that is widely segregating for zingiberenoid content. However, even in this situation, the determination of the actual 7-epi zingiberene content would need to be backstopped by a valid quantitative method.